Analiza gospodarske in okoljske trajnostnosti na Madžarskem - Sikos, T. Tamás (Urbani izziv, 2023)
Cities are the most important hubs of economic activity worldwide due to their concentration of population, businesses, trade, and stock markets. Nowadays, rapidly changing conditions resulting from factors such as globalization, industry 4.0, artificial intelligence, pandemics, and the Russian–Ukrainian war are raising new challenges for cities, which require innovative and smart solutions to maintain sustainability and competitiveness. This study analyses the performance of Hungarian cities with county rights in terms of their smartness level, with a special focus on the pillars of environmental and economic sustainability. Our hypothesis is that economically more developed cities (in terms of per capita income) are likely to be more sustainable due to the financial and professional resources available, but their ranking may not necessarily reflect the more populous group of cities due to, among other things, economies of scale and liveability. We analysed three elements of the seventeen UN Sustainable Development Goals (SDGs) and selected a set of indicators suggested by the Hungarian Central Statistical Office and the UN, adapted to the specific features of the Hungarian urban network, using min-max normalization and average calculation to construct the SDG pillars and a complex sustainability index. The cities were sorted into Five cluster groups, which mainly differ in their development dynamics and liveability. The resulting clusters reflect the spatial characteristics of the Hungarian urban network, with the dynamic cities of the western and northwestern parts of the country showing outstanding sustainability performance.
Keywords: cilji trajnostnega razvoja; economic pillar; Hungarian cities; madžarska mesta; pametna mest; smart cities; sustainability; trajnostnost